Commons as possessions: The path to protection of the commons in the ECHR system. Issue 3 (29th May 2019) - Mattei, Ugo; Albanese, Rocco Alessio; Fisher, Ryan J.
Abstract: The 'commons' is not mentioned in the texts of the European Convention on Human Rights (ECHR) or Article 1 of Protocol No. 1 (P‐1). This essay argues that 'possessions' — which does appear in the latter — should be interpreted by the European Court of Human Rights (ECtHR) to protect commons against national governments' undue interferences. The argument comprises two parts. First, we analyse the polysemic term 'possessions' to show how the current understanding of this category is marred by flawed assumptions and by false dichotomies. Then, we propose an 'ecological' construction of legal relationships between subjects and objects. We find support in the ECtHR case law on Article 8. We argue this approach should be extended to Article 1 P‐1: once disentangled from possessive individualism and market paradigms, 'possessions' encompass the commons and the category offers a solid legal basis toward the justiciability in Strasbourg of privatisations.